PENGARUH PENGELUARAN PEMERINTAH BIDANG BANTUAN SOSIAL DAN KESEHATAN, KONSUMSI RUMAH TANGGA DAN PENDIDIKAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI INDONESIA - Tamara, Yosi; Yeniwati, Yeniwati (Universitas Negeri Padang, 2020)
Abstract : This study explains the effect of government spending on social and health assistance on HDI, household consumption of HDI and education about HDI in Indonesia. This study combines cross-sectional data in 33 provinces with a time series from 2014-2018, with the Regression Panel method with Effective Effect model selection tests. The results showed that: (1) Government expenditure on social assistance has a positive and not significant effect on the human development index in Indonesia, (2) Government expenditure on health has a positive and significant effect on the human development index in Indonesia (3) House consumption the ladder has a positive and significant effect on the human development index in Indonesia, (4) Education has a positive and significant effect on the human development index in Indonesia.Keyword:Government expenditure on social assistance and health, household consumption, education and human development index.